Genotypic variation in rice root system distribution and activity in response to short-term soil drought - Kameoka, Emi; Mitsuya, Shiro; Suralta, Roel R.; Yamauchi, Akira; Henry, Amelia (J-STAGE, 2023)
In this study, two experiments were conducted to evaluate the genotypic variation of rice root system distribution and root activity in response to short-term drought conditions. Seven rice genotypes were used, of which one (Rexmont) showed the greatest reduction in shoot biomass under drought, and two (Swarna and KDML105) showed the least reduction in shoot biomass under drought in both experiments. In a phytotron experiment (Experiment 1) in which root hydraulic conductivity (Lpr) of 21-day-old rice plants was evaluated in well-watered (control) and dry down (drought) conditions, the Lpr of Swarna, KDML105, and IRAT109 were significantly lower under drought compared to the control. In a field experiment (Experiment 2) conducted in the 2013 wet season at IRRI, stomatal conductance, bleeding rate, and root surface area density (RSAD) at 0-15, 15-30, 30-45, and 45-60 cm soil depths were measured in an irrigated (control) and rainfed (drought) treatments. Swarna, KDML105, and FR13A showed significant reductions in RSAD at 0-30 cm depth under drought in the field compared to the control, while Rexmont and IRAT109 showed no significant changes. In addition, Rexmont and Swarna both maintained higher bleeding rates than the other genotypes. Based on the root hydraulic and architectural traits of contrasting genotypes, we conclude that the bleeding rate did not explain the genotypic variations in the maintenance of shoot biomass, and that reducing shallow root growth and Lpr in response to drought conferred the best ability to maintain shoot biomass under short-term drought conditions.